Antecedents of internal reputation and its consequences on organizational outcomes: a systematic review - Lee, Ling Hooi; Abdullah, Zulhamri (Emerald Publishing, 2024)
Purpose – Organizational reputation has come to the forefront amidst today’s increasingly competitive business environment. While the perspectives of external stakeholders continue to generate research attention among reputation scholars, perceptions of internal stakeholders like employees deserve similar or more focus due to their ability to sway external organizational reputation. Thoroughly understanding organizational variables that precede internal reputation perceptions among employees and the ensuing consequences enables effective reputation management measures. This study aims to develop a comprehensive framework that outlines the antecedents and consequences of the internal reputation concept. Design/methodology/approach – The Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) 2020 review protocol was applied. Around 24 journal articles were drawn from the Web of Science and Scopus databases and analyzed using qualitative content analysis. Findings – The review revealed 31 constructs related to the internal reputation concept, which were categorized into seven main themes, and a comprehensive framework was developed. Future research recommendations include the need to expand the study’s parameters, adopt a different research method and target varied contexts to achieve a more exhaustive systematic literature review on internal reputation. Research limitations/implications – This study attempts to contribute to the understanding of the internal reputation concept, theories and reputation management practices through its findings. Originality/value – This paper provides the first known systematic literature review of the internal reputation concept, which could provide practical guidance to professionals in internal reputation management and academic guidance for future research in internal reputation.